Increased kynurenine concentration attenuates serotonergic neurotoxicity induced by 3, 4-methylenedioxymethamphetamine (MDMA) in rats through activation of aryl hydrocarbon receptor. (1st April 2021) - Abuin-Martínez, C.; Vidal, R.; Gutiérrez-López, M.D.; Pérez-Hernández, M.; Giménez-Gómez, P.; Morales-Puerto, N.; O'Shea, E.; Colado, M.I.
Abstract: 3, 4-Methylenedioxymethamphetamine (MDMA) is an amphetamine derivative that has been shown to produce serotonergic damage in the brains of primates, including humans, and of rats. Tryptophan, the precursor of serotonin, is primarily degraded through the kynurenine (KYN) pathway, producing among others KYN, the main metabolite of this route. KYN has been reported as an endogenous agonist of the aryl hydrocarbon receptor (AhR), a transcription factor involved in several neurological functions. This study aims to determine the effect of MDMA on the KYN pathway and on AhR activity and to establish their role in the long-term serotonergic neurotoxicity induced by the drug in rats. Our results show that MDMA induces the activation of the KYN pathway, mediated by hepatic tryptophan 2, 3-dioxygenase (TDO). MDMA also activated AhR as evidenced by increased AhR nuclear translocation and CYP1B1 mRNA expression. Autoradiographic quantification of serotonin transporters showed that both the TDO inhibitor 680C91 and the AhR antagonist CH-223191 potentiated the neurotoxicity induced by MDMA, while administration of exogenous l -kynurenine or of the AhR positive modulator 3, 3′-diindolylmethane (DIM) partially prevented the serotonergic damage induced by the drug. The results demonstrate for the first time that MDMA increases KYN levels and AhR activity, and these changes appear to play a role in limiting the neurotoxicity induced by the drug. This work provides a better understanding of the physiological mechanisms that attenuate the brain damage induced by MDMA and identify modulation of the KYN pathway and of AhR as potential therapeutic strategies to limit the negative effects of MDMA. Graphical abstract: Image 1 Highlights: - MDMA increases hippocampal and plasma KYN levels through activation of hepatic TDO. - MDMA neurotoxicity is potentiated by a TDO inhibitor and attenuated by KYN + probenecid. - MDMA induces a short-term increase in hippocampal AhR activation. - CH-223191, an AhR antagonist, potentiates MDMA-induced serotonergic neurotoxicity. - DIM, a positive modulator of AhR, attenuates MDMA-induced serotonergic neurotoxicity.